Sho1 and Msb2 Play Complementary but Distinct Roles in Stress Responses, Sexual Differentiation, and Pathogenicity of Cryptococcus neoformans - So, Yee-Seul; Jang, Juyeong; Park, Goun; Xu, Jintao; Olszewski, Michal A.; Bahn, Yong-Sun (Frontiers in Microbiology, 2018)
The high-osmolarity glycerol response (HOG) pathway is pivotal in environmental-stress response, differentiation, and virulence of Cryptococcus neoformans, which causes fatal meningoencephalitis. A putative membrane sensor protein, Sho1, has been postulated to regulate HOG pathway, but its regulatory mechanism remains elusive. In this study we characterized the function of Sho1 with relation to the HOG pathway in C. neoformans. Sho1 played minor roles in osmoresistance, thermotolerance, and maintenance of membrane integrity mainly in a HOG-independent manner. However, it was dispensable for cryostress resistance, primarily mediated through the HOG pathway. A mucin-like transmembrane protein, Msb2, which interacts with Sho1 in Saccharomyces cerevisiae, was identified in C. neoformans, but found not to interact with Sho1. MSB2 codeletion with SHO1 further decreased osmoresistance and membrane integrity, but not thermotolerance, of sho1 mutant, indicating that both factors play to some level redundant but also discrete roles in C. neoformans. Sho1 and Msb2 played redundant roles in promoting the filamentous growth in sexual differentiation in a Cpk1-independent manner, in contrast to the inhibitory effect of the HOG pathway in the process. However, both factors contributed independently to Cpk1 phosphorylation during vegetative growth and endoplasmic reticulum (ER)-stress response. Finally, Sho1 and Msb2 play distinct but complementary roles in the pulmonary virulence of C. neoformans. Overall, Sho1 and Msb2 play complementary but distinct roles in stress response, differentiation, and pathogenicity of C. neoformans.